Pengaruh Merek Islami terhadap Loyalitas Pelanggan pada Nasabah Bank Syariah di Kota Bandung - Ratih Hurriyati; Girang Razati; Kharisma Sumiati (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2021)
This study aims to determine how much the Islamic brand affects customer loyalty of Islamic Bank customers in the city of Bandung. The type of research used is descriptive verification by describing the variables studied and then drawing conclusions. The research object are the dependent variable is Customer Loyalty and Islamic Brands as independent variables. The population in this study using Sharia Bank customers in the city of Bandung. Sampling in this study using the Simple Random Sampling method (taking random samples) to 165 respondents. The instrument test was carried out by validity and reliability testing and the technique used was path analysis with computer software tools SPSS 24.0 for Windows and Microsoft Excel. 2010 for Windows 7. Based on the overall research results through path analysis, it shows the calculation results are greater than those in the table. This means that overall there is a significant effect of Islamic Brand on customer Customer Loyalty. In an effort to increase loyalty, Islamic Banks need to increase branding according to the sub-variables in Islamic Brands.Keywords: Islamic Branding, Customer Loyalty